2007
DOI: 10.1016/j.plefa.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Improved quantification of prostaglandins in biological samples by optimizing simultaneously the relationship eicosanoid/internal standard and using liquid chromatography tandem mass spectrometry

Abstract: Although a wide variety of articles on quantification of eicosanoids by using internal standards are published every year, little has been done on how much internal standard should be added. This article demonstrates that the application of experimental design enables estimating the interaction eicosanoid/internal-standard and to select confidently an optimal amount of internal standard and a response factor (RF) for the analysis of eicosanoids in a high number of samples, where the amount of sample is limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Table 4 shows that the number of publications on the use of uniform shell designs and LC-MS is less compared to the above mentioned chromatographic techniques. Most of the applications have focused on modeling the internal standard response factor as a function of the analyte and internal standard concentrations [65,66] and on determining the optimal recovery conditions of developed analytical methods [67][68][69]. Articles regarding instrumental optimization are mainly concerned with the 3 factors such as x 1 : sheath gas flow, x 2 : ESI needle voltage and x 3 : pH of the mobile phase [70] or x 1 : MS gas flow rate, x 2 : MS nebulizer gas pressure and x 3 : LC flow rate [13].…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 99%
“…Table 4 shows that the number of publications on the use of uniform shell designs and LC-MS is less compared to the above mentioned chromatographic techniques. Most of the applications have focused on modeling the internal standard response factor as a function of the analyte and internal standard concentrations [65,66] and on determining the optimal recovery conditions of developed analytical methods [67][68][69]. Articles regarding instrumental optimization are mainly concerned with the 3 factors such as x 1 : sheath gas flow, x 2 : ESI needle voltage and x 3 : pH of the mobile phase [70] or x 1 : MS gas flow rate, x 2 : MS nebulizer gas pressure and x 3 : LC flow rate [13].…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 99%
“…In a recent comparative study between the internal standard and the traditional calibration method by using LCMS/MS [9], it is reported that the degree of ionization in the electro-spray ion source is strongly dependent on the amount of molecules resulting in a non-linearity in the concentration/response ratio. It must be said, that several quantitative studies [10][11][12] have demonstrated the variability of the RF as a direct result of varying the analyte and internal standard concentrations indicating clearly that among the possible variables affecting the RF accuracy, the interaction analyte/internal-standard could play an important role which is generally omitted in quantification studies.…”
Section: Response Factor Accuracy and Recoverymentioning
confidence: 99%